A prewetting induced underwater superoleophobic or underoil (super) hydrophobic waste potato residue-coated mesh for selective efficient oil/water separation. Issue 2 (15th September 2015) - Li, Jian; Li, Dianming; Yang, Yaoxia; Li, Jianping; Zha, Fei; Lei, Ziqiang
Abstract : Light or heavy oil and water mixtures can by separated selectively with high efficiency using potato residue coated meshes. Abstract : Oil/water separation has recently become a worldwide challenge due to expanding industrial oily wastewater and frequent oil spill accidents. The development of a low-cost, biobased, and environmentally friendly material has been attempted to treat environmentally sensitive water pollution caused by oils. Herein, prewetting induced underwater superoleophobic or underoil (super) hydrophobic waste potato residue coated-mesh (PRCM) without any further chemical modification was demonstrated for the first time for selective oil/water separation, which was fabricated by spraying waste potato residue powders (PRP) and waterborne polyurethane (PU) mixtures on a stainless steel mesh. After the PRCM is prewetted with water, water can be removed from the light oil/water mixture by gravity with high separation efficiency. On the other hand, heavy oil can be removed from the oil/water mixture by gravity via the heavy oil prewetted PRCM. The as-prepared PRCM showed a high separation efficiency of above 96.5% for a series of light or heavy oil–water mixtures. In addition, the PRCMs maintained a high separation efficiency of over 98.0% and a stable recyclability even after 40 separation cycles for a kerosene–water mixture. Furthermore, the as-prepared PRCM exhibited excellent environmental stability under a series of harsh conditions that were used for the separation of mixtures of oil and various corrosive materials, including strong acidic, alkaline and salt aqueous solutions.